PENGEMBANGAN MODUL PEMBELAJARAN IPA 2 UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA YANG TERINTEGRASI MAHASISWA PENDIDIKAN IPA FKIP UST - Septi Ambarwati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
The aim of this study is to develop IPA 2 learning Module for the topic of The Microscope that can improve the 2012/2013 class students at the Department of Science Education Yogyakarta Sarjanawiyata Tamansiswa UniversityÂ  in understanding the concept of integrated science. This study was a research and development study by using the design of the 4-D model consisting of defining, designing, developing, and disseminating stages. Subjects were 27 students of 4th semester at the 2012/2013 class of Department of Science Education Yogyakarta Sarjanawiyata Tamansiswa University. The results form an integrated IPA 2 learning modules to enhance the 4th semester student at Department of Science Education Yogyakarta Sarjanawiyata Tamansiswa University in understanding the science concepts. Media validation, material validation, testing one-on-one, small group testing, and field trials obtained good in overall criteria. The concept understanding of the students has increased significantly, derived from the value of midsemester and endsemester examination.